Improve the performance of CZTSSe solar cells by applying a SnS BSF layer - Omrani, Mir Kazem; Minbashi, Mehran; Memarian, Nafiseh; Kim, Dae-Hwan (Solid-state electronics, 2018)
•Highest achieved efficiency for CZTSSe.•Comparison and validation of simulation with an experimental case.•Proposing a simple, experimentally available and structurally matched BSF to increase the efficiency.•Optimization of the BSF layer parameters. In this study, the CZTSSe (Cu2ZnSn(S,Se)4) solar cells, with Al/ZnO:Al/ZnO (i)/CdS/CZTSSe/Mo structure, have been simulated. The simulation results have been compared and validated with real experimental results. Next, suggestions for improving the performance of CZTSSe solar cell have been provided. A SnS layer has been used as back surface field (BSF) layer. Different physical parameters of SnS layer are investigated, and the optimum values are selected. It has been found that by inserting a BSF layer with optimum parameters, the efficiency of CZTSSe solar cell increases from 12.3% to 17.25% due to enhancement of both short-circuit current density (Jsc) and open circuit voltage (Voc). For this optimized cell structure, the maximum Jsc =  37.37 mA/cm2, Voc =  0.605 V, and fill factor = 76.28% are obtained under 1.5 AM illumination.